The Vibrant Spectra of the Oceans: Unravelling the Diversity, Functions, and Applications of Seaweed Pigments - Freitas, Marta V. (2025)
Seaweeds are photosynthetic organisms that harvest sunlight and convert it into essential energy through a highly effective biochemical process powered by light, which in turn is captured and directed to the reactive centers by pigments. Seaweed pigments are fundamental to the seaweed photosynthetic process and are also responsible for their current taxonomic classification into three distinct divisions. The Chlorophyta comprises the green seaweeds, which hold high levels of both chlorophyll a and b, along with lesser amounts of β-carotene and xanthophylls. The Ochrophyta integrates the brown seaweeds (class Phaeophyceae), which are particularly rich in the xanthophyll fucoxanthin, while also showing lower levels of other xanthophylls, chlorophyll a and c, and β-carotene. The Rhodophyta houses the red seaweeds, which are characterized by holding high levels of phycoerythrin, as well as lower quantities of phycocyanin, chlorophyll a, β-carotene, and xanthophylls. However, regardless of their designation, seaweed species exhibit a significant range of colors and hues that go beyond “green,” “brown,” and “red,” rendering them visually unique, due to the relative composition and abundance of each pigment within their living cells. Nowadays, science has unveiled not only the diversity of these pigments, but also their biological function. Targeted extraction methods and potential end-use applications for these pigments have been researched and developed, with the resulting product often designed to protect and promote human health. Today, humankind acknowledges the benefits of natural products obtained from the oceans, including those obtained from seaweed pigments. This chapter aims to supply insight on the diversity, functions, and applications of the pigments found in all the three divisions, thus contributing to a greater understanding of the benefits these functional molecules can provide to humanity.